Partnering Ethics and Chemistry in Secondary and University STEM Education via an Innovatively Designed Periodic Table of Chemical Elements - Bramstedt, Karina (Acta Bioethica, 2020)
As declared by the United Nations, 2019 is the International Year of the Periodic Table of Chemical Elements. Accordingly, an innovative new Periodic Table of Chemical Elements and Ethics [PETE] has been developed as an educational tool for secondary and university STEM (Science, Technology, Engineering and Mathematics) education. The tool is designed to be used in a case-based approache that is feasible to both individual and small group learners. Specifically, with the new periodic table, STEM becomes aligned with STSE (Science and Technology on Society and Environment), laying a curricular pathway for integrating discussions of ethics into the teaching of chemistry. Presented is the table, as well as sources for pairable ethics cases, and guidance for teachers to create curriculum which facilitates connections between ethics, chemistry, and society.